Induction of micronuclei in broad snouted caiman (Caiman latirostris) hatchlings exposed in vivo to Roundup® (glyphosate) concentrations used in agriculture - López González, Evelyn Cecilia (2013)
Caiman latirostris is one of the two crocodilian species living in Argentina. As a result of agricultural expansion produced in recent years, some populations are exposed to continuous pesticide discharge due to the proximity of its natural geographic distribution to extensive agricultural areas. The aim of this study was to evaluate genotoxicity and the effects on growth of Roundup® (RU; glyphosate based formulation) on C. latirostris hatchlings, considering concentrations commonly applied in crops and subsequently decay of the compound in water through time, as it might occur in the environment. C. latirostris 20 days old, from three different clutches, were exposed to two RU concentrations in plastic containers, during two months. RU concentration was progressively decreased through time, so experimental groups were: treatment 1: 11mg/l (concentration at the beginning) to 2,5mg/l (concentration at the end of experiment), treatment 2: 21mg/l to 5mg/l; and a control without RU. At the end of exposure period, blood samples were obtained and the micronucleus (MN) test applied in erythrocytes as a marker of genotoxicity. Results indicated a significant increase in the frequency of MN (p <0.05) and a tendency to lower growth in the groups exposed to RU compared to the negative control. These results, together with those reported in previous studies; warn about the effect that C. latirostris wild populations continuously exposed to low concentrations of pesticides might be suffering.